Celebrity Endorsement and Purchase Intentions: The Role Of Trust, Attractiveness, Suitability Product - Wulandari, Widya; Septrizola, Whyosi (JURNAL PUNDI, 2021)
The purpose of this study was to analyze The Effect of Trustworthiness on Attractiveness on endorsement products and the Effect of Product suitability on endorsement products on Rachel Venya on Purchase Intention of Undergraduate students in the city of Padang. This type of research is a causative research. The population of this study were all undergraduate students in the city of Padang who followed Rachel Venya's Instagram account, the number of which was unknown. purposive sampling method. The number of samples is 120 people. The data used are primary and secondary data obtained through distributing questionnaires to tourists. The analytical method used is descriptive and inductive analysis through multiple regression analysis. The results show that: Trust does not have a significant positive effect on Purchase Intention, research attractiveness does not have a significant effect on Purchase Interest in support products and product compatibility has a significant positive effect on Purchase Interest in Rachel's program support products for undergraduate students in the city of Padang.